(untitled) (Asian Education Studies, 2017)
Pilot program on vocational guidance and social integration of individuals disabled since childhood. Ninety disabled people selected to participate in the program, have received professional orientation at 15 organizations and businesses within Moscow, and taken psychological trainings dedicated to social adaptation in real working teams. Analysis of psychological testing prior to commencing the program and final or ‘exit’ testing, combined with the results of the participants employment (43% have been employed), are valid confirm effectiveness of the program. Analysis of psychological testing prior to commencing the program and final or ‘exit’ testing, combined with the results of the participants employment (43% have been employed), are valid confirm effectiveness of the program. Based on these results, replicative methodology that facilitates employment for individuals with different forms of disability may be designed and suggests further areas of work.